Challenges in preserving the “good doctor” norm: physicians' discourses on changes to the medical logic during the initial wave of the COVID-19 pandemic - Härgestam, Maria; Jacobsson, Maritha; Bååthe, Fredrik; Brulin, Emma (Frontiers in Psychology, 2023)
Introduction The COVID-19 pandemic was a tremendous challenge to the practice of modern medicine. In this study, we use neo-institutional theory to gain an in-depth understanding of how physicians in Sweden narrate how they position themselves as physicians when practicing modern medicine during the first wave of the pandemic. At focus is medical logic, which integrates rules and routines based on medical evidence, practical experience, and patient perspectives in clinical decision-making. Methods To understand how physicians construct their versions of the pandemic and how it impacted the medical logic in which they practice, we analyzed the interviews from 28 physicians in Sweden by discursive psychology. Results The interpretative repertoires showed how COVID-19 created an experience of knowledge vacuum in medical logic and how physicians dealt with clinical patient dilemmas. They had to find unorthodox ways to rebuild a sense of medical evidence while still being responsible for clinical decision-making for patients with critical care needs. Discussion In the knowledge vacuum occurring during the first wave of COVID-19, physicians could not use their common medical knowledge nor rely on published evidence or their clinical judgment. They were thus challenged in their norm of being the “good doctor”. One practical implication of this research is that it provides a rich empirical account where physicians are allowed to mirror, make sense, and normalize their own individual and sometimes painful struggle to uphold the professional role and related medical responsibility in the early phases of the COVID-19 pandemic. It will be important to follow how the tremendous challenge of COVID-19 to medical logic plays out over time in the community of physicians. There are many dimensions to study, with sick leave, burnout, and attrition being some interesting areas.